Managing football organizations: a man's world? Comparing women in decision-making positions in Germany and Norway and their international influence: a contextual approach. (2nd January 2017) - Strittmatter, Anna-Maria; Skirstad, Berit
Abstract : This research examines the representation of females in the executive committees of the national football associations of Germany and Norway and their international influence. Pettigrew's contextual approach to change is used to identify the change process in governance, with a focus on pressures from outside and within sport in general and especially within football, the key actors, their values and legitimacy, and the structures and the strategies of the organizations. The analysis is based on secondary sources and interviews. The women's football teams in these two countries have been relatively successful and while the national football associations may appear similar and also atypical of most countries; important differences between them are to be found in the speed of the changes associated with different cultures and the different ways in which the two football federations elect their executive boards. In Europe, the big clubs see the added value of having women's teams.